2013
DOI: 10.1590/s1415-47572013005000009
|View full text |Cite
|
Sign up to set email alerts
|

Crude alkaloid extract of Rhazya stricta inhibits cell growth and sensitizes human lung cancer cells to cisplatin through induction of apoptosis

Abstract: There is an urgent need to improve the clinical management of non-small cell lung cancer (NSCLC), one of the most frequent causes of cancer-related deaths in men and women worldwide. Rhazya stricta, an important medicinal plant used in traditional Oriental medicine, possesses anti-oxidant, anti-carcinogenic and free radical scavenging properties. This study was done to explore the potential anticancer activity of a crude alkaloid extract of R. stricta (CAERS) against the NSCLC line A549. CAERS markedly suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 53 publications
2
34
0
Order By: Relevance
“…This may be attributed to indole alkaloids in R. stricta which have been found to possess numerous biological activities and anticancer potentiality (Gilani et al, 2007). It has been found that a crude alkaloid extract from R. stricta inhibited cell growth and sensitized human lung cancer cells, A549, to cisplatin through induction of apoptosis (Elkady, 2013). Photomicrograph of liver tissue section of rat in HCC group showed hepatic parenchyma with foci of anaplastic hepatocellular carcinoma as well as other foci of cystic cholangio carcinoma associated with areas of telangictasis with haemorrhage as well as individual hepatocellular necrosis (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This may be attributed to indole alkaloids in R. stricta which have been found to possess numerous biological activities and anticancer potentiality (Gilani et al, 2007). It has been found that a crude alkaloid extract from R. stricta inhibited cell growth and sensitized human lung cancer cells, A549, to cisplatin through induction of apoptosis (Elkady, 2013). Photomicrograph of liver tissue section of rat in HCC group showed hepatic parenchyma with foci of anaplastic hepatocellular carcinoma as well as other foci of cystic cholangio carcinoma associated with areas of telangictasis with haemorrhage as well as individual hepatocellular necrosis (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…This may be the underlying mechanism for the reduction of these tumor markers by R. stricta extract supplementation. Also, it has been found that a crude alkaloid extract from R. stricta inhibited cell growth and sensitized human lung cancer cells, A549, to cisplatin through induction of apoptosis (Elkady, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…[24] Briefly, fresh R. stricta leaves were washed and dried under shade. Dried leaves (350 g) were soaked in 80% ethanol for three days and then filtered and evaporated using a rotary evaporator (Buchi, Switzerland).…”
Section: Plant Materialsmentioning
confidence: 99%
“…An equal volume of chloroform was added, and the solution was shaken for 3 h. Finally, two layers were formed, one the chloroform layer, from which alkaloids were extracted, and the other the aqueous layer, from which non-alkaloids were extracted; the separate contents of both layers were immediately freeze-dried. [24] Preparation of whole aqueous extract from R. stricta leaves WAE was prepared according to our laboratory protocol as described by Kabli et al [23] In brief, washed fresh leaves of R. stricta were cut into small pieces and 96 g were taken along with 1 L of distilled water in a blender The mixture was left for 24 h in a shaker at room temperature. The mixture was later filtered with filter paper (125 mm), and then with membrane filters (0.22 mm).…”
Section: Plant Materialsmentioning
confidence: 99%
“…For rNa extraction and reverse transcriptase-pcr, gene-specific primers were used as previously described 26,27 .…”
Section: Rna Extraction and Quantitative Rt-pcrmentioning
confidence: 99%